Migration Discourse in German and Italian Newspapers: an Interlingual Data-driven Study - Brambilla, Marina; Flinz, Carolina (ANNALI. SEZIONE GERMANICA. Rivista del Dipartimento di Studi Letterari, Linguistici e Comparati dell’Università degli studi di Napoli L’Orientale, 2021)
The following study is intended as a contribution to interlingual discourse analyses. We used an ad hoc comparable corpus including press texts from newspapers representing different political orientations ("Die Zeit"; "Süddeutsche Zeitung"; "Focus"; "La Repubblica"; "La Stampa"; "Libero Quotidiano") in order to show how the discourse on migration is shaped in both countries Germany and Italy. We will focus on the recurrence of selected competing lexemes - Asylant (‘asylum seeker’), Asylbewerber (‘asylum seeker’), Asylsuchender (‘asylum seeker’), Einwanderer (‘immigrant’), Flüchtling (‘refugee’), Geflüchteter (‘refugee’), Immigrant (‘immigrant’), Migrant (‘immigrant’), Vertriebener (‘displaced person’), Zuwanderer (‘immigrant’) and immigrato (‘immigrant’), migrante, (‘immigrant‘), profugo (‘refugee’), richiedente asilo (‘asylum seeker’), rifugiato (‘refugee’) - and on their preferred combinations. Considering the fact that specific lexemes or the choice of a collocation can activate frames and different cognitive metaphors (see among others Fillmore 1982 and Lakoff/Johnson 1980), we will use this approach to shed light on the similarities and differences between the respective discourses on migration.